STRATEGIES TO IMPROVE THE ECONOMY OF SUKAMENAK VILLAGE COMMUNITY AMID THE COVID-19 PANDEMIC THROUGH DIGITAL MSMES - Fatonah, Siti; Al-Arbi, M Fathurrahman (Nindikayla Institute, 2024)
This article aims to elaborate on Micro Small and Medium Enterprises (MSMEs) during the Covid-19 pandemic. The Covid-19 pandemic has made the majority of economic sectors, especially MSMEs, stagnant. The excesses of most MSMEs cannot develop and many end up in setbacks and even bankruptcy. This makes MSME business people in Sukamenak Village, Baros District, change their sales strategy through digitalization schemes. This digitalization scheme educates the public about utilizing market places (intermediaries) and using social media as a marketing technique. In addition, digital MSMEs must synergize with netizens in the marketing of products and services. Thus the digital MSME development scheme in Sukamenak Village can be one of the alternatives to save business people amid the Covid-19 pandemic. This article uses the method of devotional study by elaborating on various literature on the development of digital MSMEs. This article argues that the development of digital MSMEs has become an alternative rescue and the development of digital entrepreneurship in Indonesia through digital MSMEs during the Covid-19 pandemic